Surplus sludge treatment in two sludge treatment beds under subtropical condition in China. (April 2017) - Hu, Shanshan; She, Xuanlou; Wei, Xiandong; Hu, Bo; Hu, Chengxiao; Qian, Yunqiu; Fang, Yinghong; Zhang, Xirui; Bashir, Safdar; Chen, Zhongbing
Abstract: Sludge treatment bed has been used for sludge dewatering and stablilization due to the low operating and maintenance costs. However, there are still limiting information of this technology compare to conventional technologies, and very few information on using this technology in developing countries. In the present study, two sludge treatment beds were investigated under seven sludge loading rates and feeding frequencies under subtropical condition in China. The results showed that plants play an important role for sludge dewatering and stablilization. The best loading rate and feeding frequency for sludge dewatering and stablilization was 10L/4d in the planted system, with TS (total solid) and VS (volatile solid)/TS contents were 29% and 25%, respectively. The best pollutants removal efficiencies in leachate was observed at 12L/4d in the planted system, which were 99.8%, 91.1%, 98.6%, and 91.5% for COD (chemical oxygen demand), NH4 + -N, TN (total nitrogen), and TP (total phosphorus), respectively. Heavy metals concentrations in the leachate were below the Chinese integrated wastewater discharge standard. In the accumulated sludge, TN + TP + TK (total potassium) > 30 g/kg which fulfill the standard of Chinese sludge for agriculture reuse. The bioavailability of Cu, Ni, Cr, Fe, and Pb was low thanks to the high proportion in residual state and oxidation state. However, Cd needs to be considered before the treated sludge can be applied for agriculture in China. Highlights: Sludge treatment beds were investigated in the subtropical condition in China. Residual sludge is rich in N, P, and K for agriculture usage. Bioavailability of Cu, Ni, Cr, Fe, and Pb is low due to the high proportion in residual state and oxidation state. Cd needs to be considered before the treated sludge can be applied in agriculture.